PENGEMBANGAN MEDIA ASESMEN FORMATIF BERBASIS GIMKIT DENGAN MODEL FOUR-D UNTUK MENINGKATKAN PARTISIPASI SISWA PADA MATERI MUKJIZAT DI MTS DARUL AMIN KOTA PALANGKA RAYA - Trisna Levia; Abdul Azis; Suci Aulia Safitri; Muhammad Kamal (CV. ADIBA AISHA AMIRA, 2024)
This study aims to develop Gimkit-based formative assessment media to increase student participation in Miracles material at MTs Darul Amin Palangka Raya. The research used the Research and Development (R&D) method with the Four-D model which includes the Define, Design, Develop, and Disseminate stages. The results showed that the use of Gimkit can significantly increase student participation, from 40% to 90%, and the average student score increased from 70 to 85. The low student participation in previous learning was caused by the use of traditional teaching methods that were less interactive. Gimkit as a gamification platform, helps students learn through a more fun and interactive approach. This research proves that the integration of technology in education, especially using a gamification platform, can be an effective solution to increase student motivation, engagement and understanding of the material being taught. This research also provides recommendations for other schools to implement gamification platforms such as Gimkit in learning.